The Butterfly Effect on Peace Education - Evelyn Cerdas-Agüero (Universidad Nacional, Costa Rica, 2012)
The objective of this paper on peace education is to generate a reflection, through the metaphor of the butterfly effect, on the importance of educating for peace during the change process of human beings and society.  It proposes education for peace as a human right, an experience and learning process that is put into practice by human beings.  It aims at changing attitudes and actions to create harmonious relationships based on the respect and recognition of human rights, and the freedom and dignity of every person.